Coding-Sequence Identification and Transcriptional Profiling of Nine AMTs and Four NRTs From Tobacco Revealed Their Differential Regulation by Developmental Stages, Nitrogen Nutrition, and Photoperiod - Liu, Lai-Hua; Fan, Teng-Fei; Shi, Dong-Xue; Li, Chang-Jun; He, Ming-Jie; Chen, Yi-Yin; Zhang, Lei; Yang, Chao; Cheng, Xiao-Yuan; Chen, Xu; Li, Di-Qin; Sun, Yi-Chen (Frontiers in Plant Science, 2018)
Although many members encoding different ammonium- and nitrate-transporters (AMTs, NRTs) were identified and functionally characterized from several plant species, little is known about molecular components for NH4+- and NO3- acquisition/transport in tobacco, which is often used as a plant model for biological studies besides its agricultural and industrial interest. We reported here the first molecular identification in tobacco (Nicotiana tabacum) of nine AMTs and four NRTs, which are respectively divided into four (AMT1/2/3/4) and two (NRT1/2) clusters and whose functionalities were preliminarily evidenced by heterologous functional-complementation in yeast or Arabidopsis. Tissue-specific transcriptional profiling by qPCR revealed that NtAMT1.1/NRT1.1 mRNA occurred widely in leaves, flower organs and roots; only NtAMT1.1/1.3/2.1NRT1.2/2.2 were strongly transcribed in the aged leaves, implying their dominant roles in N-remobilization from source/senescent tissues. N-dependent expression analysis showed a marked upregulation of NtAMT1.1 in the roots by N-starvation and resupply with N including NH4+, suggesting a predominant action of NtAMT1.1 in NH4+ uptake/transport whenever required. The obvious leaf-expression of other NtAMTs e.g. AMT1.2 responsive to N indicates a major place, where they may play transport roles associated with plant N-status and (NH4+-)N movement within aerial-parts. The preferentially root-specific transcription of NtNRT1.1/1.2/2.1 responsive to N argues their importance for root NO3- uptake and even sensing in root systems. Moreover, of all NtAMTs/NRTs, only NtAMT1.1/NRT1.1/1.2 showed their root-expression alteration in a typical diurnal-oscillation pattern, reflecting likely their significant roles in root N-acquisition regulated by internal N-demand influenced by diurnal-dependent assimilation and translocation of carbohydrates from shoots. This suggestion could be supported at least in part by sucrose- and MSX-affected transcriptional-regulation of NtNRT1.1/1.2. Thus, present data provide valuable molecular bases for the existence of AMTs/NRTs in tobacco, promoting a deeper understanding of their biological functions.